2016
DOI: 10.4155/tde-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarrier Fabrication and Macromolecule Drug delivery: Challenges and Opportunities

Abstract: Macromolecules (proteins/peptides) have the potential for the development of new therapeutics. Due to their specific mechanism of action, macromolecules can be administered at relatively low doses compared with small-molecule drugs. Unfortunately, the therapeutic potential and clinical application of macromolecules is hampered by various obstacles including their large size, short in vivo half-life, phagocytic clearance, poor membrane permeability and structural instability. These challenges have encouraged re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 107 publications
0
58
0
Order By: Relevance
“…Although the defined size ranges for microparticles (MPs) and nanoparticles (NPs) can differ based on convention and sources [43], NPs will be referred to particles within the nanometer scale (1–1000 nm) and MPs as particles in the micrometer scale (1–1000 µm) for the purpose of discussing pharmaceutical carrier formulations in this review, NPs and MPs have a variety of physicochemical properties, such as size, surface area, shape, molecular weight, porosity, hydrophobicity and charge, that allow modifications and functionalization to suit a wide range of macromolecules (Figure 4B) [24,44]. These carriers offer high loading capacity, protection from enzymes resulting in improved macromolecule stability with enhanced lung distribution and retention.…”
Section: Aerosolized Delivery Strategies For Macromolecule Drug Deliverymentioning
confidence: 99%
See 3 more Smart Citations
“…Although the defined size ranges for microparticles (MPs) and nanoparticles (NPs) can differ based on convention and sources [43], NPs will be referred to particles within the nanometer scale (1–1000 nm) and MPs as particles in the micrometer scale (1–1000 µm) for the purpose of discussing pharmaceutical carrier formulations in this review, NPs and MPs have a variety of physicochemical properties, such as size, surface area, shape, molecular weight, porosity, hydrophobicity and charge, that allow modifications and functionalization to suit a wide range of macromolecules (Figure 4B) [24,44]. These carriers offer high loading capacity, protection from enzymes resulting in improved macromolecule stability with enhanced lung distribution and retention.…”
Section: Aerosolized Delivery Strategies For Macromolecule Drug Deliverymentioning
confidence: 99%
“…For example, surface coating or functionalization improves the pharmacokinetics; particle shielding with lipids or hydrophilic polymers as polyethylene glycol (PEG) lowers the macrophages uptake and recognition, mucoadhesive particles increase the lung retention, i.e. chitosan, coating of carriers with active targeting ligands such as antibodies will be discussed later [44]. A study showed a promising PEG-co-polyester MPs delivery system, composed of co-block polymer poly(glyceroladipate-co-ω-pentadecalactone) incorporating PEG within the polymer chain, as a suitable carrier for α-chymotrypsin, a mucolytic enzyme, demonstrating high loading efficiency, retention of enzyme activity and suitability for DPI  [48].…”
Section: Aerosolized Delivery Strategies For Macromolecule Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Nanocarriers (NCs), such as liposomes, hydrogels, nanoparticles, micelles, fibers, and dendrimers, provide several advantages in delivery applications and have been extensively applied to enhance the therapeutic efficacy of drugs [1][2][3][4]. However, the major challenges in NC applications are to transport the therapeutics to the target site without significant degradation, avoid rapid phagocytic clearance, prolonging the circulation time, insufficient targeting, and limited ability to cross biological barriers such as the blood-brain barrier [1][2][3][4].…”
Section: Circulatory Cells As Drug Carriersmentioning
confidence: 99%